Fat Embolism Syndrome in Duchenne Muscular Dystrophy Patients: Early Recognition and Aggressive Therapy - Lee D. Murphy; Mouhammad Yabrodi; Riad Lutfi (Case Reports in Critical Care)
We describe two pediatric patients with Duchenne muscular dystrophy that presented with acute neurologic deterioration and hypoxic respiratory failure requiring mechanical ventilation. These cases fulfill the clinical criteria for Fat Embolism Syndrome. Early recognition and aggressive supportive therapy with mechanical ventilation, right ventricular afterload reduction, and blood transfusion led to survival without any residual effects from the event. Fat Embolism Syndrome needs to be considered early in the course of patients with Duchenne muscular dystrophy who present with respiratory and neurological symptoms.